Optimizing fluconazole-embedded transfersomal gel for enhanced antifungal activity and compatibility studies - Cheng, Zhiqiang; Kandekar, Ujjwala; Ma, Xiaoshi; Bhabad, Vishal; Pandit, Ashlesha; Liu, Liming; Luo, Jiping; Munot, Neha; Chorage, Trushal; Patil, Abhinandan; Patil, Sandip; Tao, Liang (Frontiers in Pharmacology, 2024)
Fungal infections are of major concern all over the globe and fluconazole is the most prevalently used drug to treat it. The goal of this research work was to formulate fluconazole-embedded transfersomal gel for the treatment of fungal infections. A compatibility study between fluconazole and soya lecithin was performed by ATR-FTIR and DSC. Transfersomes were formulated by thin film hydration technique using soya lecithin and Span 80. A central composite design was adopted to prepare different formulations. Soya lecithin and Span 80 were chosen as independent variables and the effect of these variables was studied on in-vitro drug diffusion. Formulations were evaluated for entrapment efficiency and in-vitro drug diffusion. Results of in-vitro drug diffusion were analyzed by ANOVA test. Optimized formulation was prepared based on overlay plot and evaluated by scanning electron microscopy, DSC, vesicle size, polydispersity index, zeta potential and in-vitro drug diffusion studies. Optimized formulation was loaded into xanthan gum gel base and evaluated for pH, viscosity, in-vitro and ex-vivo drug diffusion and antifungal activity. ATR-FTIR and DSC studies revealed compatibility between fluconazole and soya lecithin. Entrapment efficiency and in-vitro drug diffusion of various formulations ranged between89.92 ± 0.20 to 97.28 ± 0.42 % and 64 ± 1.56 to 85 ± 2.05 % respectively. A positive correlation was observed between in-vitro drug diffusion and Span 80, conversely, a negative correlation was noted with soya lecithin. Entrapment efficiency, particle size, zeta potential, polydispersity index and drug diffusion of optimized formulation were 95.0 ± 2.2 %, 397 ± 2 nm, -38 ± 5 mV, 0.43 and 81± 2 % respectively. SEM images showed well-distributed spherical-shaped transfersomes. In-vitro, ex-vivo drug diffusion and antifungal studies were conclusive of better diffusion and enhanced antifungal potential fluconazole in transfersomal formulation.